Lacrimal Drainage System and Nasal Cavity Melanoma after Complete Treatment of Conjunctival Melanoma - Amirreza Veisi; Zahra Dastborhan; Mohsen Dastmardi; Mozhgan Rezaie Kanavi; Saeid Rezaei (Case Reports in Ophthalmological Medicine)
Malignant melanoma of the conjunctiva is a rare tumor of the ocular surface with potential fatal consequences and a high likelihood of recurrence. Although routes for extending the tumor, including local, hematogenous, and lymphatogenous, are pretty straightforward, the indirect extension through free-floating tumoral cells to the nasolacrimal duct is not described thoroughly. We report a case of malignant melanoma of the conjunctiva which presented with local recurrence in the intranasal cavity and lacrimal sac two years after the primary surgery (without involvement of the ocular surface and punctum on the second occasion). However, there was no evidence of distant metastasis on either occasion. This case demonstrates the possible noncontiguous spreading route of melanoma tumoral cells and highlights the need for attention to the surgical technique, and careful follow-up to detect further disease activity.